Utilización de leguminosas arbustivas en la elaboración de ensilaje para la alimentación de bovinos. - Jurado Zurita, Franklin Argenis (2022)
Cattle represent a herd of cattle domesticated by man for their use and production. In other words, this group includes various herbivorous mammals domesticated to meet specific nutritional or economic needs. At the global level, beef production is booming since there is no mechanical-industrial development completed in several of the world's continents, which has affected the scarcity of pasture, accompanied by global warming, giving rise to extreme droughts. In Ecuador, livestock is one of the most demanded and important activities in the food sector, and those responsible for it must be prepared with all the knowledge and training in terms of their production. Therefore, the use of shrub legumes as silage was chosen as an alternative source of feed for cattle due to the benefits they provide. This research aims to record the benefits of using these legumes in the production of silage for cattle feeding. Where interpretive and exploratory methods of existing bibliographic data will be used in scientific journals, web pages, scientific articles, knowing that this exploratory technique of data compilation is the most. The legumes named above offer many benefits to the production system in combination with grass and other additives that optimize the nutritional benefits of this food.